2020
DOI: 10.3390/ijms21010339
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Role of Bicarbonate Transporters and Associated Carbonic Anhydrase Enzymes in Maintaining Ion and pH Homeostasis in Non-Secretory Organs

Abstract: The bicarbonate ion has a fundamental role in vital systems. Impaired bicarbonate transport leads to various diseases, including immune disorders, cystic fibrosis, tumorigenesis, kidney diseases, brain dysfunction, tooth fracture, ischemic reperfusion injury, hypertension, impaired reproductive system, and systemic acidosis. Carbonic anhydrases are involved in the mechanism of bicarbonate movement and consist of complex of bicarbonate transport systems including bicarbonate transporters. This review focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 142 publications
(193 reference statements)
0
29
0
Order By: Relevance
“…These transporters are of particular interest in cancer research because CO 2 -dependent acid production from high metabolism and excessive glycolysis corresponds to approximately half of the extracellular acids that cancer cells generate (13). Studies on cultured cancer cells in vitro or implanted in vivo have identified NBC-mediated acid extrusion mechanisms in a variety of cancer cells and their involvement in cell growth and progression (2,14). Notably, NBCn1/SLC4A7 was identified as a new marker for human breast cancer (15) and its contribution to cancer progression has been recognized in MCF17 breast cancer cells (16,17) and breast cancer cells from patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…These transporters are of particular interest in cancer research because CO 2 -dependent acid production from high metabolism and excessive glycolysis corresponds to approximately half of the extracellular acids that cancer cells generate (13). Studies on cultured cancer cells in vitro or implanted in vivo have identified NBC-mediated acid extrusion mechanisms in a variety of cancer cells and their involvement in cell growth and progression (2,14). Notably, NBCn1/SLC4A7 was identified as a new marker for human breast cancer (15) and its contribution to cancer progression has been recognized in MCF17 breast cancer cells (16,17) and breast cancer cells from patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…CAs are an important family of enzymes that catalyze the conversion of CO 2 into HCO 3 − to regulate the pH balance of the blood. [37][38][39].…”
Section: Comparison Of Gene Expression Levels Of Control and Mutant Gmentioning
confidence: 99%
“…CAs work "in tandem" with NBC1 [65] that introduces the bicarbonate produced by the CAs into the cell. The "coordinator" of this tandem work is in the hands of membrane carbonic anhydrases that regulate the amount of bicarbonate produced and at the same time, participate in the bicarbonate transport process [66,67].…”
Section: The Phtome and How The Paradigm Appearsmentioning
confidence: 99%